2006
DOI: 10.1242/jcs.03290
|View full text |Cite
|
Sign up to set email alerts
|

PDZRN3 (LNX3, SEMCAP3) is required for the differentiation of C2C12 myoblasts into myotubes

Abstract: Summary PDZRN3 (LNX3, SEMCAP3) is required for the differentiation of C2C12 myoblasts into myotubes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 33 publications
3
52
1
Order By: Relevance
“…We previously showed that PDZRN3 is upregulated during myogenic and osteoblastic differentiation of C2C12 cells (8,11). The expression of PDZRN3 increases early (Ͻ12 h) after the induction of osteoblastic differentiation, whereas the protein is upregulated later (Ͼ48 h) after the induction of myogenic differentiation.…”
Section: Downregulation Of Pdzrn3 During Adipogenesis In 3t3-mentioning
confidence: 94%
See 4 more Smart Citations
“…We previously showed that PDZRN3 is upregulated during myogenic and osteoblastic differentiation of C2C12 cells (8,11). The expression of PDZRN3 increases early (Ͻ12 h) after the induction of osteoblastic differentiation, whereas the protein is upregulated later (Ͼ48 h) after the induction of myogenic differentiation.…”
Section: Downregulation Of Pdzrn3 During Adipogenesis In 3t3-mentioning
confidence: 94%
“…Polyclonal antibodies to PDZRN3 were generated in rabbits and purified as described previously (11). Rabbit polyclonal antibodies to C/EBP␣ (sc-61), to STAT5a (sc-1081), and to JunB (sc-73); mouse monoclonal antibodies to C/EBP␤ (sc-7692), to PPAR␥ (sc-7233), and to STAT5b (sc-1656); and goat polyclonal antibodies to aP2 (sc8661) were obtained from Santa Cruz Biotechnology (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations